Pengembangan Model Pembelajaran dengan Permainan Tradisional Engklek Sebagai Sarana Stimulasi Perkembangan Anak Usia Dini - Hidayatu Munawaroh (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
This Research aims to Know Learning Model with Traditional Games Englek As Means of Stimulation Early Childhood Development, Knowing Implementation of Learning Model with Traditional Game Engglek As Means of Stimulation of Early Childhood Development. Knowing the Learning Model with Traditional Games Engglek As Means of Stimulation Early Childhood Development. The type of research is Research Development (Research and Development). The subject of the study was a group B in RA Masythoh singkir Wonosobo. Methods of data collection research using: Observation, Interview and Documentation. The results showed: (1) learning model hopscotch game is delivered with the story with the help of posters, singing together, questions and answers, guessing pictures and play puzzle theme of various professions. (2) Implementation of Learning Model of Kpk Game which can stimulate the development aspect of group B Children in RA Masythoh Singkir Wonosobo conducted twice as many meetings accordance with RKH, the average score of indicators of child development aspect increased. The results of each average of each indicator has increased aspects of child development. (3) The effectiveness of the learning model uses effective effective games. This is supported by the results of t test calculations. He conclusion of this research is the learning model with the Traditional Engglek Games effective for the Early Childhood Stimulation Facility in RA Masythoh singkir Wonosobo, the learning model of Traditional Engglek Game